2014
DOI: 10.1086/674869
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Basis of the Migration Continuum in Brown Trout (Salmo trutta)

Abstract: Partial migration is common in many animal taxa; however, the physiological variation underpinning migration strategies remains poorly understood. Among salmonid fishes, brown trout (Salmo trutta) is one of the species that exhibits the most complex variation in sympatric migration strategies, expressed as a migration continuum, ranging from residency to anadromy. In looking at brown trout, our objective with this study was to test the hypothesis that variation in migration strategies is underpinned by physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 68 publications
1
71
1
Order By: Relevance
“…If this is also the case in brown trout, then the 600–700 years since establishment of dams corresponding to 170–200 generations should have left ample opportunities for selective responses to occur. On the other side, a recent study of trout in HAL documented that 15% of individuals aged between 1 and 3 years and with a length exceeding 12 cm left the lake and would potentially undertake migration to the sea, whereas 40% migrated into the lake and 44% remained in the tributaries [78]. Hence, a potential for long-distance migration involving anadromy seems still to be present in the population, although it is unknown if a larger proportion of individuals would have left the lake prior to the establishment of dams.…”
Section: Discussionmentioning
confidence: 99%
“…If this is also the case in brown trout, then the 600–700 years since establishment of dams corresponding to 170–200 generations should have left ample opportunities for selective responses to occur. On the other side, a recent study of trout in HAL documented that 15% of individuals aged between 1 and 3 years and with a length exceeding 12 cm left the lake and would potentially undertake migration to the sea, whereas 40% migrated into the lake and 44% remained in the tributaries [78]. Hence, a potential for long-distance migration involving anadromy seems still to be present in the population, although it is unknown if a larger proportion of individuals would have left the lake prior to the establishment of dams.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Davidsen et al (2014) found that starved sea trout postsmolts migrated further out into a fjord compared with fully fed individuals. However, Boel et al (2014) found a different pattern in their study of migration distances of brown trout in a freshwater system, where energy stores were positively correlated with migration distances. An alternative hypothesis to account for the pattern observed in this study may be that fish with poor body condition were outcompeted from the preferred shore habitats.…”
Section: Figmentioning
confidence: 90%
“…Populations in Denmark exhibit partial migration with a portion of the population in a system becoming resident and the remaining individuals migrating to the ocean (Alerstam et al, ). The decision to become a migrant or resident is driven by a variety of environmental and physiological variables including the availability of food, metabolic activity of the individual, and their condition (Thorpe et al, ; Metcalfe, ; Cucherousset et al, ; Boel et al, ), such that individuals with higher metabolic requirements and lower condition scores are more likely to undertake the migration to the ocean (Forseth et al, ; Morinville and Rasmussen, ; Boel et al, ). The process of smoltification is inherently stressful, and therefore, the choice of life‐history strategy represents a trade‐off between increased predation during migration and increased growth and reproductive potential for trout that forage in the marine environment (Hutchings and Myers, ; Klemetsen et al, ).…”
mentioning
confidence: 99%